The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1155/2016/8690593
|View full text |Cite
|
Sign up to set email alerts
|

Nasolabial Cyst Associated with Odontogenic Infection

Abstract: The nasolabial cyst or Klestadt cyst is a relatively uncommon nonodontogenic cyst that develops in the nasal alar region; it has uncertain pathogenesis. This lesion has slow growth and variable dimensions and is characterized clinically by a floating tumefaction in the nasolabial fold area around the bridge of the nose, causing an elevation of the upper lip and relative facial asymmetry. Diagnosis is primarily made clinically; if necessary, this is complemented by imaging. This paper reports the case of a 39-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 14 publications
0
8
0
3
Order By: Relevance
“…Finally, epithelial inclusion cysts of the skin may be clinically of yellowish coloration while most cases of nasolabial cysts present with normal or bluish coloration. [15][16][17] In the present case, the NC had been previously misdiagnosed as an odontogenic abscess related to the left upper incisors, which were unnecessarily extracted.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Finally, epithelial inclusion cysts of the skin may be clinically of yellowish coloration while most cases of nasolabial cysts present with normal or bluish coloration. [15][16][17] In the present case, the NC had been previously misdiagnosed as an odontogenic abscess related to the left upper incisors, which were unnecessarily extracted.…”
Section: Discussionmentioning
confidence: 66%
“…The differential diagnosis of NC includes numerous odontogenic and non-odontogenic lesions occurring in the anterior maxillary region, including radicular cyst, periapical abscess, minor salivary gland tumour, benign mesenchymal tumours, and dermoid or epidermoid cyst. [10][11][12][13][14][15][16][17] Therefore, several diagnostics methods are available to F I G U R E 1 Clinical and macroscopic features of nasolabial cyst in an older woman. (A) Extraoral examination revealed a left facial asymmetry caused by a soft painless swelling in the nasolabial fold, (B) with extension to the upper labial mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…The most common and effective treatment is complete surgical excision of the cyst, usually performed intraorally via a gingivolabial incision, under local or general anaesthesia. A transnasal approach of endoscopic marsupialisation of nasolabial cysts is described that according to some, but not all studies shows good therapeutic results. In a prospective randomised study it was concluded that both methods are effective.…”
Section: Discussionmentioning
confidence: 99%
“…In long-standing cases, the cyst wall may contain fibrous tissue. The presence of this fibrous tissue in the cyst capsule will facilitate complete enucleation (5)…”
Section: Discussionmentioning
confidence: 99%